(untitled) (Psicologia USP, 2001)
This work proposes an ethical hearing of the contemporary psychologies, from the perspective of Emmanuel Levinass ethics of radical alterity. The place of the Other, in four significant approaches of the psychological theorization and application - radical behaviorism, psychogenetics, person-centered approach and existential analysis - is identified and compared to the requirements of Levinass ethics. As a result, the inclusion of the alterity in the psychological discussion is proposed, in terms of the constitution of the subjectivity itself as well as the relation with the other of the psychological exteriority and interiority.